0179 Factor Analysis of Multidimensional Sleep Health Domains in Older Adults with Actigraphy: Results from the Einstein Aging Study. (25th May 2022) - Ji, Linying; Wallace, Meredith; Master, Lindsay; Schade, Margeaux; Zhaoyang, Ruixue; Derby, Carol; Buxton, Orfeu
Abstract: Introduction: The concept of Sleep Health, based on self-reports in the RU-SATED model, has been recently extended using parameters derived from 4 days of actigraphy in a cohort of older adults, yielding a 5-component model. Using a longer actigraphy time series from a separate study, the current factor analysis evaluates and extends a theoretically-driven, multi-dimensional sleep health construct in older adults. Methods: Participants (N=291, mean age=77.2 years, 33% males; 47% white, 40% Black, 13% Hispanic/others) enrolled in The Einstein Aging Study were included. A random subsample of 100 participants were used for exploratory factor analysis (EFA); data from the remaining participants (N=191) were used for confirmatory factor analyses (CFA). All 23 objective measures (mean 15.6 valid days +/-SD=1.2) were derived from wrist actigraphy, including 16 from the actigraphy summary statistics, and 7 from extended cosinor models. Fit of CFA models were evaluated by CFI, TLI, RMSEA, SRMR. Results: Consistent with prior research, beta was not included in the final factor structure because of its low loading on all six factors. CFA was performed on each factor and model fitting results were satisfactory (CFI > 0.94, TLI >0.92, RMSEA 90% confidence interval ranges from 0 to 0.23, and SRMR <0.05). EFA identified 6 factors, 5 consistent with prior research, and a sixth hypothesized factor (Rhythmicity) not identified previously.REGULARITY (of sleep across days): standard deviations of four sleep measures; midpoint, sleep onset time, night total sleep time (TST), and 24h TST.ALERTNESS/Sleepiness (daytime): amplitude, napping (mins and #/day).TIMING: sleep onset, midpoint, wake-time (of nighttime sleep); up-Mesor, acrophase, down-Mesor.EFFICIENCY: sleep maintenance efficiency, wake after sleep onset.DURATION: night sleep duration, night TST, 24h sleep duration, 24h TST.RHYTHMICITY (pattern across days): mesor, alpha, and minimum. Conclusion: These findings extend a multidimensional Sleep Health construct to include a Rhythmicity dimension when informed by extended objective data from older adults. Factors can be considered predictors of health outcomes, and targets for sleep interventions. Support (If Any): P01-AG003949, R01-AG062622, NIA-AG03949